Penilaian Autentik STEAM Biologi–Seni melalui Proyek Air Terjun Artifisial - Muhammad Zahrudin Afnan; Budi Utomo; widjidjono; I Putu Tony Purana (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
STEAM (Science, Technology, Engineering, Arts, and Mathematics) education has gained increasing attention as an interdisciplinary approach fostering creativity, scientific understanding, and problem-solving skills. This study aimed to evaluate students’ performance in a Biology–Art integrated STEAM project involving the construction of artificial waterfall models. A quantitative descriptive design was conducted with 43 students. Projects were assessed using eight dimensions: Design Planning, Composition and Aesthetics, Plant Elements, Animal Elements, Creativity, Neatness and Cleanliness, Functionality and Durability, and Project Presentation. Descriptive statistics and the Friedman test were used to analyze student performance across dimensions. Results showed high achievement in all dimensions, with mean scores ranging from 3.16 to 3.63 on a four-point rubric scale. Creativity achieved the highest score (M = 3.63 ± 0.49), while Composition and Aesthetics scored the lowest (M = 3.16 ± 0.72). Significant differences among dimensions were identified (χ² = 22.15, p = 0.0024), although the small effect size (Kendall’s W = 0.074) indicated relatively balanced competency development across STEAM domains. These findings show that artificial waterfall projects effectively integrate biological knowledge, artistic expression, and engineering design while developing interdisciplinary competencies.